Implementasi Undang-Undang Nomor 6 Tahun 2011 Tentang Keimigrasian : Penggunaan Izin Tinggal Kunjungan Orang Asing di Wilayah Hukum Serang - Imam Sopwan Iwan; Leo Agustino; Riswanda Riswanda (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2022)
Abstract This study tries to observe the implementation of Law No. 6 of 2011 concerning Immigration in the jurisdiction of Serang. The purpose of this study was to analyze problems related to the efforts of the Class I Immigration Office of Non TPI Serang in responding to the use of residence permits for foreign visits in the company and the obstacles faced. This study uses a contemporary qualitative analysis approach Critical Systemic Thinking with the Participatory Action Research (PAR) method. The presence of researchers in this study as the main instrument in data collection until the final report stage. Sources of data used in this study are primary data sources, such as internalization meetings or Forum Group Discussions (FGD), interviews, and narratives. The technique for determining the supporting informants is the purposive sampling technique. The results of the research from the formulation of the problem, show that there are still obstacles faced by the Immigration Office Class I Non TPI Serang in implementing Law No. 6 of 2011 concerning Immigration, such as: human resources, budget, geospatial-based data, facilities and infrastructure. Keywords: Implementation, visit stay permit, immigration.